Implementasi Kepemimpinan Kepala Sekolah dalam Meningkatkan Budaya Kerja di Madrasah Ibtidaiyah Islam Terpadu (MIIT) Roudhotul Qurro Tanjungbalai - Neliwati, Neliwati; Harahap, Carles; Fattah, Farihin Abdillah; Annisa , Raudatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to evaluate the implementation of school principal leadership in improving the work culture in the elementary madrasah. Improving and enhancing the work culture is important in order to increase the effectiveness and quality of learning in that environment. The research method used is a qualitative approach, with data obtained from interviews, observations, and documentation. Data analysis is carried out by reducing the data by summarizing the main points obtained from the reports that have been prepared and then presented to see patterns of relationships between one data and another data, and in the final stage, it is concluded. The results of the research show that the principal of MIIT Roudhotul Qurro has a personal leadership approach and is actively involved in the daily activities of the madrasah. The principal's tangible actions in addressing discipline and attendance issues reflect a strong commitment to shaping a well-organized and productive madrasah environment. Daily interactions filled with values such as cooperation, integrity, and dedication form the basis for a positive and effective work culture.